First evidence of diffuse ultra-steep-spectrum radio emission surrounding the cool core of a cluster. Issue 2 (2nd May 2018) - Savini, F; Bonafede, A; Brüggen, M; van Weeren, R; Brunetti, G; Intema, H; Botteon, A; Shimwell, T; Wilber, A; Rafferty, D; Giacintucci, S; Cassano, R; et al.
ABSTRACT: Diffuse synchrotron radio emission from cosmic ray electrons is observed at the centre of a number of galaxy clusters. These sources can be classified either as giant radio haloes, which occur in merging clusters, or as mini haloes, which are found only in cool-core clusters. In this paper, we present the first discovery of a cool-core cluster with an associated mini halo that also shows ultra-steep-spectrum emission extending well beyond the core that resembles radio halo emission. The large-scale component is discovered thanks to LOFAR observations at 144 MHz. We also analyse GMRT observations at 610 MHz to characterize the spectrum of the radio emission. An X-ray analysis reveals that the cluster is slightly disturbed, and we suggest that the steep-spectrum radio emission outside the core could be produced by a minor merger that powers electron re-acceleration without disrupting the cool core. This discovery suggests that, under particular circumstances, both a mini halo and giant halo could co-exist in a single cluster, opening new perspectives for particle acceleration mechanisms in galaxy clusters.